Theory and applications of HVAC control systems – A review of model predictive control (MPC) - Afram, Abdul; Janabi-Sharifi, Farrokh (Building and environment, 2014)
This work presents a literature review of control methods, with an emphasis on the theory and applications of model predictive control (MPC) for heating, ventilation, and air conditioning (HVAC) systems. Several control methods used for HVAC control are identified from the literature review, and a brief survey of each method is presented. Next, the performance of MPC is compared with that of other control approaches. Factors affecting MPC performance (including control configuration, process type, model, optimization technique, prediction horizon, control horizon, constraints, and cost function) are elaborated using specific examples from the literature. The gaps in MPC research are identified, and future directions are highlighted. •Reviewed the major HVAC control techniques reported in the recent literature.•Model predictive control (MPC) is reviewed in detail.•Compared the classical, hard, soft and hybrid control techniques with MPC.•Focused on the factors affecting the MPC performance with examples from literature.